Brewarrina: An Australian Story. Issue 2 (July 2015) - Austin‐Broos, Diane
Abstract This short paper discusses Barry Morris's account of the 'riot' at Brewarrina, New South Wales, in 1987 and its legal aftermath, which continued for some years. An iconic event in Australian race relations, much can be learnt from its various dimensions, a fact that Morris amply demonstrates. Notwithstanding, this discussion questions a related narrative in his book, which interprets capitalism's impact on self‐determination simply in terms of neoliberalism's 'political effects'. The paper seeks to broaden the discussion of the relations between the state and self‐determination, and between capitalism and race.